18F labeled RGD‐A7R peptide for dual integrin and VEGF‐targeted tumor imaging in mice bearing U87MG tumors. (8th October 2014) - Ma, Yufei; Liang, Sheng; Guo, Jun; Guo, Rui; Wang, Hui
<x xml:space="preserve">Abstract</x> The aim of this study is to develop a novel Arg‐Gly‐Asp acid (RGD) and Ala‐Thr‐Trp‐Leu‐Pro‐Pro‐Arg (ATWLPPR A7R) peptide‐containing ligand for 18F labeling as αvβ3 and vascular endothelial growth factor receptor‐targeted imaging agent. 18F‐RGD‐A7R was prepared by conjugation with 18F‐SFB. The final product was purified by high‐performance liquid chromatography and tested in vitro and in vivo. Cell‐binding assays of RGD‐A7R, RGD and RGD‐A7R, A7R were tested in U87MG cells (125I‐RGDyK and 125I‐A7RY as radioligand, respectively). Preliminary biodistribution of the 18F‐RGD‐A7R was also evaluated. The RGD‐A7R had good integrin binding affinity (50% inhibitory concentration (IC50) = 21.67 and 23.68 nM, slightly lower than unmodified RGD (40.02 nM) and A7R (50.18 nM)). The radiotracer had receptor‐mediated activity accumulation in U87MG tumor (1.90 ± 0.34 percentage of injected dose per gram (%ID/g) at 0.5 h postinjection), which is known to be integrin positive. After blocking with RGD‐A7R, the tumor uptake was reduced to 0.47 ± 0.06 %ID/g at 0.5 h postinjection. 18F‐RGD‐A7R exhibited dual receptor targeting properties both in vitro and in vivo. The favorable characterizations of 18F‐RGD‐A7RY, such as convenient synthesis, high specific activity, and high tumor uptake, warrant its further investigation for clinical cancer imaging.